Cost-effectiveness of monitoring glaucoma patients in shared care: an economic evaluation alongside a randomized controlled trial - Klazinga Niek S; Plochg Thomas; Lemij Hans G; van Sprundel Esther; Holtzer-Goor Kim M; Koopmanschap Marc A (BMC, 2010)
Abstract Background Population aging increases the number of glaucoma patients which leads to higher workloads of glaucoma specialists. If stable glaucoma patients were monitored by optometrists and ophthalmic technicians in a glaucoma follow-up unit (GFU) rather than by glaucoma specialists, the specialists' workload and waiting lists might be reduced. We compared costs and quality of care at the GFU with those of usual care by glaucoma specialists in the Rotterdam Eye Hospital (REH) in a 30-month randomized clinical trial. Because quality of care turned out to be similar, we focus here on the costs. Methods Stable glaucoma patients were randomized between the GFU and the glaucoma specialist group. Costs per patient year were calculated from four perspectives: those of patients, the Rotterdam Eye Hospital (REH), Dutch healthcare system, and society. The outcome measures were: compliance to the protocol; patient satisfaction; stability according to the practitioner; mean difference in IOP; results of the examinations; and number of treatment changes. Results Baseline characteristics (such as age, intraocular pressure and target pressure) were comparable between the GFU group (n = 410) and the glaucoma specialist group (n = 405). Despite a higher number of visits per year, mean hospital costs per patient year were lower in the GFU group (€139 vs. €161). Patients' time and travel costs were similar. Healthcare costs were significantly lower for the GFU group (€230 vs. €251), as were societal costs (€310 vs. €339) (p < 0.01). Bootstrap-, sensitivity- and scenario-analyses showed that the costs were robust when varying hospital policy and the duration of visits and tests. Conclusion We conclude that this GFU is cost-effective and deserves to be considered for implementation in other hospitals.